Can Tc-99m labeled erythrocyte scintigraphy be an alternative non-invasive method to endometriosis diagnosis? - Demirel, Fatih; Koca, Gokhan; Demirel, Koray; Aydogmus, Huseyin; Akbulut, Aylin; Sadic, Murat; Atilgan, Hasan Ikbal; Korkmaz, Meliha; Gokmen, Bulent (International Journal of Research in Medical Sciences, 2017)
Background: Endometriosis is defined as the implantation of endometrial gland and stroma ectopically outside the uterus. Clinically, it is a hormone dependent benign disease accompanied by pelvic pain and infertility. The aim of this study was to demonstrate the activated implants with 99m-Tc labeled erythrocyte scintigraphy (99mTc-RBCs) in patients with recurrent endometriosis and compare the results with pelvic MRI results. Methods: Patients who were diagnosed histopathologically as endometriosis either with operation and / or therapeutic laparascopy or laparotomy and, were included to present study. Thirty patients, who were diagnosed as recurrence by clinical, and laboratory terms and 10 healthy volunteer (control group) patients were included in the study. Between the second and fifth days of menstruation when the endometriotic lesions were highly activated, radionuclide imaging was performed by 99mTc-RBCs and compared with pelvic MRI findings. Results: In 27 patients out of 30 patients (90%) pathological accumulation of radioactivity foci with 99mTc-RBCs were present. The focal pathological accumulation was significant in 26 patients and moderate in 1 patient. In 22 patients (81.5%) the increased radioactivity accumulation in radionuclide images was concordant with MRI images. Regarding the MRI as reference, the sensitivity of 99mTc-RBCs was determined as 96%, specificity 29%, positive predicitive value 81% and negative predictive value was 66%. Conclusions: Imaging of endometriosis regions with 99m-Tc-RBCs can be an alternative diagnostic procedure for the patients with recurrent endometriosis.